Coffee farming business development: E-commerce technology utilization. Issue 3 (July 2021) - Panggabean, Y B S; Arsyad, M; Mahyuddin,; Nasaruddin,
Abstract: After crude oil, coffee is the most traded commodity in the world From that figure, only about 30% of the world's coffee is consumed in coffee-producing countries, the rest is exported to consuming countries such as Finland, Norway, the Netherlands, Germany and America. In recent years, total world coffee production has remained relatively constant while demand for coffee has increased significantly. Indonesia produces various types of special Arabica coffee such as Gayo coffee, Java coffee, Toraja coffee, Lintong coffee, Bajawa coffee, and Robusta coffee such as Java Robusta and Robusta Flores. Domestic coffee consumption is low, only around 3.3 million sacks of green green coffee per year. The rest, which is around 7.7 million, or about 70% of its production, both in the form of green beans and roasted coffee, is exported to Germany, USA, Japan and Italy. Of the total exports, around 25-30% are high quality Arabica coffee. E-commerce technology can play an increasingly important role in empowering such a traditional industry of agriculture. The technological underpinnings of e-commerce avail to expand the market channels of agricultural products, realizing the scale and organizational realm of agricultural product circulation, reducing the intermediaries of distribution, and reducing transaction costs. Recent studies have suggested that e-commerce helps firms to increase the information flow of agricultural products, reduce asymmetric information of farm products, and promote the creation of traceability information system for agricultural product chains. E-commerce can be part of developing a conceptual foundation for agricultural studies in the modern era and provide an understanding of the potential positive values of e-commerce.